PENGARUH KUALITAS PELAYANAN, LOKASI DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH PADA PT ASURANSI RELIANCE INDONESIA - Hendrison Hendrison; Nur Elfi Husda (Magister Manajemen STIE Bank BPD Jateng, 2020)
With the increasing number of customer complaints and to increase customer satisfaction at PT Asuransi Reliance Indonesia, researchers are interested in conducting research with service quality, location and company image variables that affect customer satisfaction. The purpose of this study was to analyze the effect of service quality, location and company image on customer satisfaction of PT Asuransi Reliance Indonesia. The method in this study is a quantitative method with a population of 845 customers, the sample was taken using a purposive sampling technique to obtain a sample of 100 respondents. The results showed that simultaneous independent variables (service quality, location and company image) significantly influence customer satisfaction. And partially the quality of service, location and company image significantly influence customer satisfaction. The three independent variables are the most dominant factors affecting customer satisfaction of PT Asuransi Reliance Indonesia. The conclusion of this study is the quality of service, location and corporate image significantly influence customer satisfaction of PT Asuransi Reliance Indonesia both partially and simultaneously.